2022
DOI: 10.1002/smll.202201275
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Synthetic Strategy for Improving Crystallinity of Zwitterionic Squaraine‐Linked Covalent Organic Frameworks with Enhanced Photothermal Performance

Abstract: Two‐dimensional covalent organic frameworks (2D COFs) offer a designable platform to explore porous polyelectrolyte frameworks with periodic ionic skeletons and uniform pore channels. However, the crystallinity of ionized 2D COF is often far from satisfactory as the electrostatic assembly of structures impedes the ordered layered arrangement. Here, a multivariate synthetic strategy to synthesize a highly crystalline squaraine (SQ)‐linked zwitterionic 2D COF is proved. A neutral aldehyde monomer copolymerizes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…Ding et al synthesized a squaraine (SQ)-linked COF as solar absorber, which also showed broad absorption from 400 to 2400 nm (Figure 5b). [32] Applying melamine foam (MF) as substrates, the SQ-COF/MF evaporator could generate vapor at 1.35 kg m À 2 h À 1 under one sun. Huang et al incorporated diketopyrrolopyrrole (DPP) into a COF backbone, which again yielded broad light absorption (Figure 5c).…”
Section: Mof/cof-based Evaporatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ding et al synthesized a squaraine (SQ)-linked COF as solar absorber, which also showed broad absorption from 400 to 2400 nm (Figure 5b). [32] Applying melamine foam (MF) as substrates, the SQ-COF/MF evaporator could generate vapor at 1.35 kg m À 2 h À 1 under one sun. Huang et al incorporated diketopyrrolopyrrole (DPP) into a COF backbone, which again yielded broad light absorption (Figure 5c).…”
Section: Mof/cof-based Evaporatorsmentioning
confidence: 99%
“…Applying monomers containing specific dye molecules is an effective approach to extend the light absorption. [32,40,41] Since 1,4,5,8-Tetrakis(phenylamino)anthracene-9,10-dione (TPAD) is known as a NIR dye, Yan et al utilized amine-functionalized TPAD as building units to synthesize a TPAD-COF (Figure 5a). [40] TPAD-COF showed a broad light absorption covering the entire UV/Vis and NIR regions as well as superhydrophilicity.…”
Section: Mof/cof-based Evaporatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Fan and Zhang et al [ 70 ] reported two photoactive SQ-linked COFs (SQ-COF-1 and SQ-COF-2), prepared through the condensation of SA with TAPB or tris(4-aminophenyl)amine (TAA). Guo et al [ 71 ] investigated the multivariate synthesis of SQ-linked COFs, Py-TPA 1-X -SQ X (X = [SA]/([TPA] + [SA])), by the reaction of 4,4′,4″,4‴-(pyrene-1,3,6,8-tetrayl) tetraaniline (TAPPy) with terephthalaldehyde (TPA) and SA. TPA was a neutral structural stabilizer.…”
Section: Classification Structures and Synthesis Of Ilcofsmentioning
confidence: 99%
“…[154] Guo et al designed a multivariate synthetic strategy to synthesize a squaraine-COF with improved crystallinity, high charge density, and exceptional chemical stability for enhanced photothermal conversion performance upon exposure to an 808 nm laser and simulated sunlight (1 kW m −2 ). [155]…”
Section: Other Applicationsmentioning
confidence: 99%